KONSEP TAâ€™ARUF BERBASIS PENDIDIKAN MULTIKULTURAL PERSPEKTIF IBNU KATSIR DALAM SURAT AL-HUJURAT AYAT 13 - Reza Rahmatulloh; Moch. Nasir; Armuza, Munif (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Taâ€™aruf means â€œto get acquaintedâ€ or â€œto know each otherâ€. It comes from the Arabic word â€œtaâ€™aarafaâ€. Knowing this is not just limited to knowing the name. In Islam, taâ€™aruf is a process of getting to know someone closely, both Muslims and non-Muslims. In the context of marriage, taâ€™aruf is an attempt to recognize a life partner before marriage. The author chooses the method of literature research. Therefore, the technique used in data collection is the collection of literal data, namely: library materials that are coherent with the object of discussion in question. The right data collection technique in library research is to collect books, papers, articles, magazines, journals, and so on. This step is usually known as the documentation method. The concept of Taâ€™aruf in the perspective of multicultural education in the interpretation of Ibn Katsirâ€™s Tafsir in sura al-Hujurat verse 13, i.e. taâ€™aruf in the concept of the Qurâ€™an is not as simple as what is understood today. Taâ€™aruf itself is not only interpreted as a process of introduction that is synonymous with marriage. Taâ€™aruf is interpreted as a suggestion to get to know each other between fellow human beings, not limited to Muslims or other non-Muslims. The process of taâ€™aruf offered by the Qurâ€™an bridges the occurrence of good interactions and the establishment of a harmonious relationship and heterogeneity (diversity).